(untitled) (Boletin Médico de Postgrado, 2020)
According to the WHO, tuberculosis represents one of the top ten causes of death worldwide and is the number one cause of death from a single infectious agent. The incidence of tuberculosis has decreased an average of 1.5% annually since the year 2000, however the impact of the SARS-CoV-2 pandemic could delay the diagnosis and treatment of new cases of TB. We report the case of a 26-year-old male who consulted for fever, weight loss and dysphonia with a duration of 6 months. BK and sputum cultures were negative for M. tuberculosis. The patient is referred to the Otorhinolaryngology and Facial Surgery Clinic of the Dr. Luis Gomez Lopez University Hospital where a nasofibrolaryngoscopy is performed showing an epiglottis with an irregular surface that extends to the arytenoids and interarytenoid zone and edematous ventricular bands that do not allow visualization of vocal folds. Laryngeal microsurgery is performed to obtain a biopsy sample. Histopathology reveals proliferation of newly formed vessels, intervascular spaces occupied by macrophages and lymphocytes, presence of multiple nodular lesions formed by epithelloid macrophages surrounded by a halo of lymphocytes and numerous giant Langerhans cells. Diagnosis of laryngeal tuberculosis is made and antituberculous treatment is initiated.